Performance improvement, design and preparation method of FRP aggregate concrete recycled from retired fan blades

By using epoxy mortar wrapping modification treatment in the FRP aggregate concrete recycled from decommissioned wind turbine blades, and determining the replacement rate and wrapping amount in combination with formulas (1) to (6), the insufficiency in mechanical properties of FRP aggregate concrete in the existing technology is solved. Stability issues enable the preparation of high-performance concrete and the recycling of retired wind turbine blades.

CN119328895AActive Publication Date: 2025-01-21SHENZHEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411495641.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The mechanical properties of FRP aggregate concrete recovered from existing retired fan blades are unstable and cannot meet the actual engineering application standards. It is impossible to directly determine the substitution rate and epoxy mortar wrapping of modified FRP aggregates based on compressive strength indicators and mix ratios. quantity.

Method used

Through formulas (1) to (6), according to the preset compressive strength and mix ratio of concrete, the replacement rate and wrapping amount are determined, and the recycled FRP material is wrapped and modified with epoxy mortar to obtain modified recycled FRP aggregate. Used to prepare concrete containing modified recycled FRP aggregate.

Benefits of technology

The parameters of the pre -stress intensity determine the concrete preparation process, ensure the preparation of a modified recycling FRP aggregate concrete with the target pressure resistance, and improve the mechanical performance of recycling FRP concrete, and meet the needs of high -performance building materials. And promote the cycle of the leaves of retired wind turbines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328895A_ABST
    Figure CN119328895A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete aggregate, and particularly relates to a performance improvement, design and preparation method of FRP aggregate concrete recycled from retired fan blades. The method comprises the following steps: firstly, through formulas (1)-(6), determining the substitution rate of modified FRP aggregate and the wrapping amount of epoxy mortar in the concrete preparation process according to the preset compressive strength and the mixing ratio of concrete; then preparing the modified recycled FRP aggregate according to the wrapping amount of the epoxy mortar; and finally, preparing the concrete containing the modified recycled FRP aggregate by adopting the modified recycled FRP aggregate. Therefore, according to the preparation method provided by the invention, the parameters of the preparation process can be determined according to the preset compressive strength of the concrete, so that the preparation of the concrete containing the modified recycled FRP aggregate with the target compressive strength is realized. Meanwhile, the problems that in the prior art, FRP waste is difficult to treat, and the resource utilization rate is low are solved, environmental pollution is effectively reduced, and cyclic utilization of the retired wind driven generator blade is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete aggregates, and in particular relates to a method for improving the performance, designing and preparing FRP aggregate concrete recycled from retired wind turbine blades. Background Art

[0002] With the rapid development of the construction industry, the use of traditional building materials has put tremendous pressure on the environment. The excessive consumption of resources such as cement, river sand, and natural coarse aggregate has not only led to resource depletion, but also increased carbon emissions. Fiber reinforced composites (FRP) are used to manufacture wind turbine blades due to their advantages such as high strength, light weight, corrosion resistance, and fatigue resistance. As wind power is an important component of new clean energy, with the replacement of equipment and the expiration of the service life of early units, the FRP waste generated by retired wind turbine blades is increasing. However, for the FRP waste in retired wind turbine blades, the traditional landfill and incineration treatment methods are not only costly, but also cause serious pollution to the environment. If the FRP waste in retired wind turbine blades is recycled and used in the preparation of concrete, it can not only reduce the huge harm to the environment caused by improper treatment of waste FRP in retired wind turbine blades, but also reduce the over-exploitation of resources such as sand and gravel. Therefore, in order to promote the green recycling of FRP waste in retired wind turbine blades, it is very important to continue to promote the research and utilization of FRP aggregate concrete recycled from retired wind turbine blades.

[0003] However, in the existing preparation scheme of FRP aggregate concrete recycled from retired wind turbine blades, directly adding untreated FRP aggregate recycled from retired wind turbine blades will cause the strength and elastic modulus of concrete to decrease, resulting in unstable mechanical properties of the prepared FRP aggregate concrete recycled from retired wind turbine blades, which cannot meet the application standards of actual projects. Therefore, it is necessary to perform surface modification treatment on FRP waste recycled from retired wind turbine blades to improve the mechanical properties of FRP aggregate concrete recycled from retired wind turbine blades.

[0004] The strength of the modified FRP aggregate concrete recycled from retired wind turbine blades prepared by wrapping FRP waste recycled from retired wind turbine blades with epoxy mortar is improved compared with that of the unmodified FRP aggregate concrete recycled from retired wind turbine blades. However, in the current design process of the modified FRP aggregate concrete recycled from retired wind turbine blades, the replacement rate of the modified FRP aggregate recycled from retired wind turbine blades and the epoxy mortar wrapping amount cannot be directly determined by the compressive strength index of the modified FRP aggregate concrete recycled from retired wind turbine blades and the mix ratio of the concrete, so that the preparation of the concrete material with the preset compressive strength index cannot be realized. Summary of the invention

[0005] The purpose of the present invention is to provide a performance improvement, design and preparation method for FRP aggregate concrete recycled from retired wind turbine blades. The preparation method provided by the present invention can determine the parameters of its preparation process by the preset compressive strength of the concrete, thereby achieving the preparation of concrete containing modified recycled FRP aggregates with a target compressive strength, thereby promoting the recycling of retired wind turbine blades.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing concrete containing modified recycled FRP aggregate, comprising the following steps:

[0008] According to formulas (1) to (6), based on the preset compressive strength and mix ratio of the concrete containing the modified recycled FRP aggregate, the replacement rate and the encapsulation amount of the concrete containing the modified recycled FRP aggregate are obtained; the replacement rate is the volume percentage of the modified recycled FRP aggregate in the coarse aggregate of the concrete containing the modified recycled FRP aggregate, the modified recycled FRP aggregate is the recycled FRP aggregate modified by epoxy mortar, and the encapsulation amount is the mass ratio of the epoxy mortar to the recycled FRP aggregate;

[0009]

[0010] k s1 =1+0.449s 2 +0.928rs-0.699s(3);

[0011]

[0012] k s2 =-78.696s 2 -1.326rs+47.359s-5.921(5);

[0013]

[0014] In formulas (1) to (6): f c ' is the compressive strength of concrete containing modified recycled FRP aggregate, f co ' is the compressive strength of concrete with natural aggregate, ε c ' is the peak strain of concrete containing modified recycled FRP aggregate, r is the substitution rate, k s1 k is the elastic modulus of concrete related to the amount of wrapping, s2 is the peak strain coefficient of concrete related to the encapsulation amount, s is the encapsulation amount, E c is the elastic modulus of concrete containing modified recycled FRP aggregate, k e is the elastic modulus coefficient of concrete related to the replacement rate;

[0015] According to the wrapping amount, the recycled FRP material is wrapped and modified with epoxy mortar to obtain the modified recycled FRP aggregate;

[0016] According to the replacement rate and the mix ratio, the modified recycled FRP aggregate is used to prepare the concrete containing the modified recycled FRP aggregate, and the compressive strength of the concrete containing the modified recycled FRP aggregate is greater than or equal to the preset compressive strength.

[0017] Preferably, the method for determining the replacement rate and the package quantity comprises the following steps:

[0018] The compressive strength of the concrete containing modified recycled FRP aggregate is preset, the preset compressive strength of the concrete containing modified recycled FRP aggregate is obtained, and the mix ratio of the concrete containing modified recycled FRP aggregate is determined; the compressive strength of the concrete containing natural aggregate is obtained from the mix ratio, and the range of two parameters, the replacement rate and the encapsulation amount, is obtained by using formulas (1) to (6), wherein the range is the range when the compressive strength of the concrete containing modified recycled FRP aggregate is ≥ the preset compressive strength under the condition of the determined mix ratio; and then the replacement rate and the encapsulation amount of the concrete containing modified recycled FRP aggregate are determined from the range of the two parameters, the replacement rate and the encapsulation amount.

[0019] Preferably, the wrapping amount is 0.1 to 0.5.

[0020] Preferably, the replacement rate is ≥ 30%.

[0021] Preferably, the epoxy mortar includes epoxy resin, a curing agent and an additive; the additive includes cement and quartz sand.

[0022] Preferably, the mass ratio of the epoxy resin, the curing agent and the auxiliary agent is (1-2): (1-5): (12-20).

[0023] Preferably, the mass ratio of cement to quartz sand in the additive is 1:(1-3).

[0024] Preferably, the particle size of the recycled FRP material is in the range of 5 to 25 mm, and the aspect ratio is less than 1.6.

[0025] Preferably, the packaging modification comprises the following steps:

[0026] premixing the recycled FRP material and an additive to obtain a premix;

[0027] The epoxy resin and the curing agent are mixed and then mixed with the premix to obtain an initial modified product;

[0028] The initial modified product is cured to obtain the modified recycled FRP aggregate.

[0029] Preferably, the water-cement ratio in the mix is ​​0.45.

[0030] Preferably, the curing conditions for preparing the concrete containing the modified recycled FRP aggregate include: a curing temperature of 20±2° C., a relative humidity of 95%, and a curing time of 28 days.

[0031] The present invention provides a method for preparing concrete containing modified recycled FRP aggregate. The present invention first determines two other key parameters in the concrete preparation process, namely, the replacement rate and the encapsulation amount, by the preset compressive strength and mix ratio of the concrete through formulas (1) to (6). Then, according to the encapsulation amount, the recycled FRP material is encapsulated and modified by epoxy mortar to obtain the modified recycled FRP aggregate; finally, according to the replacement rate and mix ratio, the modified recycled FRP aggregate is used to prepare the concrete containing the modified recycled FRP aggregate, and the compressive strength of the obtained concrete containing the modified recycled FRP aggregate is ≥ the preset compressive strength. Therefore, the preparation method provided by the present invention can determine the parameters of its preparation process by the preset compressive strength of the concrete, thereby realizing the preparation of concrete containing modified recycled FRP aggregate with the target compressive strength. At the same time, the preparation method provided by the present invention is simple, and the recycled FRP waste is modified and used as aggregate in the preparation of concrete, which significantly improves the mechanical properties (including strength and elastic modulus) of the recycled FRP-concrete, meeting the demand for high-performance building materials. At the same time, it solves the problems of difficult FRP waste treatment and low resource utilization in the existing technology, effectively reduces environmental pollution, and promotes the recycling of retired wind turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the gradation curve of recycled GFRP aggregate and natural coarse aggregate;

[0033] Figure 2 The relationship between the replacement rate and compressive strength of recycled FRP aggregate concrete at different replacement rates in the embodiment;

[0034] Figure 3 Comparison between the experimental and predicted stress-strain curves of concrete containing recycled GFRP aggregates;

[0035] Figure 4 The core compressive strength comparison of modified recycled GFRP aggregate concrete in the examples;

[0036] Figure 5 Comparison between the experimental and predicted stress-strain curves of concrete containing modified recycled GFRP aggregates;

[0037] Figure 6This is a schematic diagram of the relationship between the replacement rate of GFRP aggregates recycled from modified retired wind turbine blades, the epoxy mortar coating amount, and the compressive strength of concrete containing GFRP aggregates recycled from modified retired wind turbine blades when the compressive strength of ordinary concrete (i.e., concrete with natural aggregates) is 35 MPa in a preferred embodiment of the method for determining the compressive bearing capacity of concrete with recycled GFRP aggregates of the present invention. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing concrete containing modified recycled FRP aggregate, comprising the following steps:

[0039] According to formulas (1) to (6), based on the preset compressive strength and mix ratio of the concrete containing the modified recycled FRP aggregate, the replacement rate and the encapsulation amount of the concrete containing the modified recycled FRP aggregate are obtained; the replacement rate is the volume percentage of the modified recycled FRP aggregate in the coarse aggregate of the concrete containing the modified recycled FRP aggregate, the modified recycled FRP aggregate is the recycled FRP aggregate modified by epoxy mortar, and the encapsulation amount is the mass ratio of the epoxy mortar to the recycled FRP aggregate;

[0040]

[0041] k s1 =1+0.449s 2 +0.928rs-0.699s(3);

[0042]

[0043] k s2 =-78.696s 2 -1.326rs+47.359s-5.921(5);

[0044]

[0045] In formulas (1) to (6): f c ' is the compressive strength of concrete containing modified recycled FRP aggregate, f co ' is the compressive strength of concrete with natural aggregate, ε c ' is the peak strain of concrete containing modified recycled FRP aggregate, r is the substitution rate, k s1 k is the elastic modulus of concrete related to the amount of wrapping, s2 is the peak strain coefficient of concrete related to the encapsulation amount, s is the encapsulation amount, E c is the elastic modulus of concrete containing modified recycled FRP aggregate, k e is the elastic modulus coefficient of concrete related to the replacement rate;

[0046] According to the wrapping amount, the recycled FRP material is wrapped and modified with epoxy mortar to obtain the modified recycled FRP aggregate;

[0047] According to the replacement rate and the mix ratio, the modified recycled FRP aggregate is used to prepare the concrete containing the modified recycled FRP aggregate, and the compressive strength of the concrete containing the modified recycled FRP aggregate is greater than or equal to the preset compressive strength.

[0048] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0049] In the present invention, the raw materials for preparing concrete include coarse aggregate, fine aggregate, cement and water. The raw materials for preparing the concrete with natural aggregate are all natural coarse aggregate. The raw materials for preparing the concrete containing recycled FRP aggregate are recycled FRP aggregate or recycled FRP aggregate and natural coarse aggregate. The raw materials for preparing the concrete containing modified recycled FRP aggregate are modified recycled FRP aggregate or modified recycled FRP aggregate and natural coarse aggregate.

[0050] In the present invention, the replacement rate is the replacement rate of modified recycled FRP aggregate. The wrapping amount is the epoxy mortar wrapping amount.

[0051] In the present invention, the raw materials for preparing the concrete containing modified recycled FRP aggregate include cement, water, coarse aggregate and natural fine aggregate. The coarse aggregate in the concrete containing modified recycled FRP aggregate is modified recycled FRP aggregate, or is modified recycled FRP aggregate and natural coarse aggregate.

[0052] In the present invention, the raw materials for preparing the natural aggregate concrete include cement, water, natural coarse aggregate and natural fine aggregate.

[0053] In the present invention, the mix ratio of the concrete with natural aggregate is the mass ratio of cement, water, natural coarse aggregate and natural fine aggregate. The one-to-one correspondence between the mix ratio of the concrete with natural aggregate and the compressive strength of the concrete with natural aggregate can be determined by literature data.

[0054] In the present invention, the replacement rate is the modified FRP aggregate replacement rate, and the wrapping amount is the epoxy mortar wrapping amount.

[0055] The present invention obtains the replacement rate and the encapsulation amount of the concrete containing the modified recycled FRP aggregate according to the preset compressive strength and the mix ratio of the concrete containing the modified recycled FRP aggregate according to formulas (1) to (6); the replacement rate is the volume percentage of the modified recycled FRP aggregate in the coarse aggregate of the concrete containing the modified recycled FRP aggregate, the modified recycled FRP aggregate is the epoxy mortar modified recycled FRP aggregate, and the encapsulation amount is the mass ratio of the epoxy mortar to the recycled FRP aggregate.

[0056] In the present invention, the method for constructing formulas (1) to (6) includes the following steps:

[0057] Providing concrete specimens, the concrete specimens comprising concrete specimens of natural aggregates, concrete specimens containing recycled FRP aggregates, and concrete specimens containing modified recycled FRP aggregates;

[0058] The concrete specimens are subjected to a compression test to obtain initial compressive strength information of the concrete specimens containing natural aggregates, alternative compressive strength information of the concrete specimens containing recycled FRP aggregates, and modified compressive strength information of the concrete specimens containing modified recycled FRP aggregates;

[0059] According to the initial compressive strength information and the replacement compressive strength information, construct an initial formula correlating the compressive strength of concrete with natural aggregates, the compressive strength of concrete containing recycled FRP aggregates, and the replacement rate of recycled FRP aggregates, wherein the replacement rate of recycled FRP aggregates is the volume percentage of recycled FRP aggregates in the coarse aggregates of the concrete specimen containing recycled FRP aggregates;

[0060] According to the initial compressive strength information and the modified compressive strength information, formulas (2) to (6) are constructed;

[0061] Formulas (2) to (6) are used to correct the initial formula to obtain formulas (1) to (6).

[0062] The present invention provides concrete specimens, which include concrete specimens of natural aggregates, concrete specimens containing recycled FRP aggregates, and concrete specimens containing modified recycled FRP aggregates. In the present invention, the raw materials for preparing the concrete specimens include coarse aggregates, fine aggregates, cement, and water, and the mix ratios of the concrete specimens of natural aggregates, the concrete specimens containing recycled FRP aggregates, and the concrete specimens containing modified recycled FRP aggregates are the same; the coarse aggregates of the concrete specimens of natural aggregates are natural coarse aggregates, the coarse aggregates of the concrete specimens containing recycled FRP aggregates are recycled FRP aggregates, or a mixture of recycled FRP aggregates and natural coarse aggregates, and the coarse aggregates of the concrete specimens containing modified recycled FRP aggregates are modified recycled FRP aggregates, or a mixture of modified recycled FRP aggregates and natural coarse aggregates. According to the "Concrete Physical and Mechanical Properties Test Method Standard" GB / T50081-2019, "Construction Pebbles and Crushed Stones" GB / T14685-2011, and "Construction Sand" GB / T 14684-2011, the present invention selects and prepares the natural coarse aggregate, natural fine aggregate and recycled FRP aggregate required for the above-mentioned concrete specimens, determines the concrete specimen mix ratio, and the experimental process ensures that the gradation of FRP aggregate and gravel (natural coarse aggregate) is consistent. In the present invention, the above-mentioned concrete specimens (ordinary concrete specimens with the same mix ratio (i.e., concrete specimens of natural aggregates), ordinary recycled FRP aggregate concrete specimens (i.e., concrete specimens containing recycled FRP aggregates), and modified recycled FRP concrete specimens (i.e., concrete specimens containing modified recycled FRP aggregates)) can be prepared, or can be provided in advance.

[0063] When preparing the above-mentioned concrete specimens according to the present invention, cement, sand (natural fine aggregate), gravel (natural coarse aggregate), water and recycled FRP aggregate are prepared separately according to the determined mix ratio. Ensure that the quality of each material meets the standard requirements. Add cement, sand, gravel, water and recycled FRP aggregates to the mixer in sequence. Start the mixer and stir evenly until all materials are fully mixed to form a uniform concrete mixture. The stirring time and speed are adjusted according to the specific requirements of the concrete to ensure the uniformity and fluidity of the mixture. Pour the mixed concrete into a mold and vibrate it to make it dense. Vibration can be carried out by mechanical vibration to discharge the bubbles inside the concrete and improve the density and strength of the concrete. After curing for twenty-eight days under standard curing conditions, the above-mentioned concrete specimens are obtained.

[0064] In the present invention, the mix ratios of cementitious materials (cement), coarse aggregates and fine aggregates among the above-mentioned ordinary concrete specimens, ordinary recycled FRP aggregate concrete specimens at the recycled FRP aggregate replacement rate, and epoxy mortar-wrapped modified recycled FRP aggregate concrete specimens at the replacement rate are the same. In other words, the mix ratio of ordinary concrete specimens is determined, that is, fine aggregates (sand), coarse aggregates (stones) and cementitious materials (cement) of a certain aggregate gradation are selected, the proportion of fine aggregates (sand) in ordinary recycled FRP aggregate concrete specimens and modified recycled FRP aggregate concrete specimens is consistent with that of ordinary concrete, and the coarse aggregates in ordinary recycled FRP aggregate concrete specimens and modified recycled FRP aggregate concrete specimens replace part or all of the coarse aggregates according to the corresponding replacement rate.

[0065] After obtaining the concrete specimens, the present invention performs a compressive test on the concrete specimens to obtain initial compressive strength information of the concrete specimens containing natural aggregates, alternative compressive strength information of the concrete specimens containing recycled FRP aggregates, and modified compressive strength information of the concrete specimens containing modified recycled FRP aggregates.

[0066] The present invention conducts a compression test on ordinary concrete specimens (i.e., concrete specimens with natural aggregates) to obtain the initial compressive strength information of the concrete specimens with natural aggregates. The present invention conducts compression tests on various ordinary recycled FRP aggregate concrete specimens (i.e., concrete specimens containing recycled FRP aggregates) at different recycled FRP substitution rates to obtain the corresponding replacement compressive strength information of the concrete specimens containing recycled FRP aggregates. The epoxy mortar coating amount of each of the various recycled FRP aggregate concretes at different recycled FRP aggregate substitution rates is obtained; according to the epoxy mortar coating amount, a compression test is conducted on the modified recycled FRP aggregate concrete (i.e., concrete specimens containing modified recycled FRP aggregates) at the corresponding modified recycled FRP aggregate substitution rate to obtain the corresponding modified compressive strength information of each of the various modified recycled FRP aggregate concretes.

[0067] The present invention conducts uniaxial compression tests on ordinary concrete, corresponding ordinary recycled FRP aggregate concretes, and corresponding modified recycled FRP aggregate concretes, thereby obtaining the initial strength of ordinary concrete (which may be the average value of multiple groups as shown in Table 2), the recycled FRP aggregate replacement rate and replacement strength of each ordinary recycled FRP aggregate concrete (which may be the average value of multiple groups at the replacement rate as shown in Table 2), and the epoxy mortar dosage and modified strength of each modified recycled FRP aggregate concrete (which may be the average value of multiple groups at the dosage as shown in Table 3).

[0068] In the present invention, after obtaining the modified recycled FRP aggregate concrete specimen, the present invention further needs to conduct a uniaxial compression test to obtain the stress-strain curve, compressive strength, elastic modulus, etc. of the modified recycled FRP-concrete time, and evaluate the mechanical properties of the modified recycled FRP aggregate concrete time.

[0069] After obtaining the initial compressive strength information, the alternative compressive strength information and the modified compressive strength information, the present invention constructs an initial formula for the compressive strength of concrete associated with natural aggregates, the compressive strength of concrete containing recycled FRP aggregates and the replacement rate of recycled FRP aggregates according to the initial compressive strength information and the alternative compressive strength information, wherein the replacement rate of recycled FRP aggregates is the volume percentage of recycled FRP aggregates in the coarse aggregates of the concrete specimen containing recycled FRP aggregates; constructs formulas (2) to (6) according to the initial compressive strength information and the modified compressive strength information; and uses formulas (2) to (6) to correct the initial formulas to obtain formulas (1) to (6).

[0070] The present invention first obtains the initial compressive strength information of ordinary concrete specimens, the corresponding replacement compressive strength information of ordinary recycled FRP aggregate concrete specimens under the recycled FRP replacement rate, and the modified compressive strength information of modified recycled FRP aggregate concrete specimens under the corresponding recycled FRP aggregate replacement rate; according to the initial compressive strength information and the replacement compressive strength information, an initial formula between the strength of ordinary concrete and the corresponding strength of ordinary recycled FRP aggregate concrete under any recycled FRP aggregate replacement rate is constructed; according to the modified compressive strength information and the initial equation, a target formula (formula (1) to (6)) for the initial compressive strength of ordinary concrete, the compressive strength of modified recycled FRP aggregate concrete, the recycled FRP aggregate replacement rate and the epoxy mortar coating amount is constructed.

[0071] In the present invention, based on the initial compressive strength information and the replacement compressive strength information, an initial formula between the initial compressive strength of ordinary concrete and the replacement compressive strength of ordinary recycled FRP aggregate concrete under any corresponding replacement rate of recycled FRP aggregate is constructed, specifically including:

[0072] The initial compressive strength information and various alternative compressive strength information under different recycled FRP aggregate replacement rates are analyzed to obtain the first coefficient of the recycled FRP aggregate replacement rate; based on the first coefficient, an initial formula between the initial compressive strength of ordinary concrete and the corresponding alternative compressive strength of ordinary recycled FRP aggregate concrete under any recycled FRP aggregate replacement rate is generated.

[0073] The initial compressive strength of ordinary concrete and the corresponding modified compressive strength of modified recycled FRP aggregate concrete at a specific substitution rate under different epoxy mortar coating amounts are obtained; based on the initial compressive strength of ordinary concrete and the modified compressive strength of modified recycled FRP aggregate concrete at multiple specific substitution rates, the quadratic function relationship between the initial compressive strength of ordinary concrete and the modified compressive strength of modified recycled FRP aggregate concrete at a specific substitution rate is obtained.

[0074] Obtain the modified compressive strength information of modified recycled FRP aggregate concrete under the modified recycled FRP aggregate replacement rate, including:

[0075] The epoxy mortar coating amounts of various recycled FRP aggregate concretes under different recycled FRP replacement rates were obtained; according to the epoxy mortar coating amounts, the modified recycled FRP aggregate concretes under the corresponding modified recycled FRP replacement rates were subjected to compressive tests to obtain the corresponding modified strength information of various modified recycled FRP aggregate concretes.

[0076] According to the modified strength information and the initial equation, a target equation between the initial strength of the ordinary concrete, the compressive strength of the modified recycled FRP aggregate concrete, the replacement rate of the recycled FRP and the epoxy mortar coating amount is constructed, specifically including: according to the quadratic function relationship (Formulas 2 to 6), a target formula (Formula 1) for the initial strength of the ordinary concrete, the compressive strength of the modified recycled FRP aggregate concrete, the replacement rate of the modified recycled FRP and the epoxy mortar coating amount is obtained.

[0077] The present invention analyzes the relationship among unmodified ordinary concrete without recycled FRP aggregate substitution, ordinary recycled FRP aggregate concrete with a certain recycled FRP aggregate substitution rate, and modified recycled FRP aggregate concrete wrapped with epoxy mortar at the same recycled FRP aggregate substitution rate, and determines the mathematical relationship among the strength of modified recycled FRP aggregate concrete, the initial strength of ordinary concrete, and the epoxy mortar wrapping amount at a certain recycled FRP aggregate substitution rate. Under the conditions of given initial strength of ordinary concrete and recycled FRP aggregate substitution rate, the strength of ordinary recycled FRP aggregate concrete can be accurately calculated, and the required epoxy mortar wrapping amount can be accurately calculated according to the target strength of the modified recycled FRP aggregate concrete and the target bearing capacity of the concrete beam prepared therefrom.

[0078] In a specific embodiment of the present invention, the method for determining the replacement rate and the package quantity comprises the following steps:

[0079] The compressive strength of the concrete containing the modified recycled FRP aggregate (i.e., the preset compressive strength) is preset, and the mix ratio of the concrete containing the modified recycled FRP aggregate is determined; the compressive strength of the concrete containing the natural aggregate is obtained from the mix ratio, and the range of two parameters, the replacement rate and the encapsulation amount, is obtained by using formulas (1) to (6), wherein the range is the range when the compressive strength of the concrete containing the modified recycled FRP aggregate is ≥ the preset compressive strength under the condition of the determined mix ratio; then, the replacement rate and the encapsulation amount of the concrete containing the modified recycled FRP aggregate are determined from the range of the two parameters, the replacement rate and the encapsulation amount.

[0080] In the present invention, the wrapping amount is preferably 0.1 to 0.5, and most preferably 0.3.

[0081] In the present invention, the substitution rate is ≥ 30%.

[0082] After obtaining the wrapping amount, the present invention uses epoxy mortar to wrap and modify the recycled FRP material according to the wrapping amount to obtain the modified recycled FRP aggregate.

[0083] In the present invention, the method for preparing the modified recycled FRP material preferably comprises the following steps:

[0084] The recycled FRP material and epoxy mortar are mixed and packaged and modified to obtain the modified recycled FRP material; the epoxy mortar includes epoxy resin, curing agent and auxiliary agent.

[0085] The present invention has no special requirements for the source of the recycled FRP material, and it can be obtained by methods well known in the art. In a specific embodiment of the present invention, the recycled FRP material is specifically recycled FRP waste from retired wind turbine blades. The present invention preferably pre-treats the recycled FRP material, and the pre-treatment preferably includes crushing, screening, washing and drying in sequence. The present invention has no special requirements for the specific implementation methods of the crushing, screening, washing and drying. The present invention removes the dust of resin and filler on the surface of the recycled FRP material by washing. In the present invention, the particle size range of the recycled FRP material is preferably 5 to 25 mm; the aspect ratio is preferably <1.6. In a specific embodiment of the present invention, the recycled FRP material is specifically recycled GFRP material.

[0086] In the present invention, the curing agent is preferably an epoxy resin curing agent. The auxiliary agent preferably includes cement and quartz sand; the mass ratio of the cement to the quartz sand is preferably 1:(1-3), and specifically 1:2 in the embodiment. The mass ratio of the epoxy resin, the curing agent and the auxiliary agent is preferably (1-2):(1-5):(12-20), and specifically 1:3:16 in the embodiment.

[0087] In a specific embodiment of the present invention, the wrapping amount is specifically 0.25:1, 0.3:1 or 0.35:1.

[0088] In the present invention, the package modification preferably comprises the following steps:

[0089] premixing the recycled FRP material and an additive to obtain a premix;

[0090] The epoxy resin and the curing agent are mixed and then mixed with the premix to obtain an initial modified product;

[0091] The initial modified product is cured to obtain the modified recycled FRP material.

[0092] In the present invention, the recycled FRP material and the additive are premixed to obtain a premix. The premixing is preferably carried out in a mixer, and the stirring time of the premixing is preferably 1 to 2 minutes. In the present invention, the additive is preferably covered on the surface of the recycled FRP material by premixing.

[0093] In the present invention, the epoxy resin and the curing agent are first stirred and mixed to obtain an epoxy resin mixture; and the epoxy resin mixture and the premix are second stirred and mixed to obtain an initial modified product. In the present invention, the second stirring and mixing time is preferably 3 to 5 minutes.

[0094] After obtaining the initial modified product, the present invention cures the initial modified product to obtain the modified recycled FRP material. In the present invention, the curing preferably includes a first stage curing and a second stage curing. The temperature of the first stage curing is preferably room temperature, and the time is preferably 48 hours. Between the first stage curing and the second stage curing, the present invention preferably stirs the product obtained by curing the initial modified product in the first stage, and the time of the stirring treatment is preferably 1 minute. The present invention preferably separates part of the material bonded together due to a small amount of epoxy mortar between the particles through a stirring treatment between the first stage curing and the second stage curing. The temperature of the second stage curing is preferably room temperature, and the time is preferably 7 days.

[0095] After obtaining the modified recycled FRP aggregate, the present invention uses the modified recycled FRP aggregate to prepare the concrete containing the modified recycled FRP aggregate according to the replacement rate and mix ratio, and the compressive strength of the concrete containing the modified recycled FRP aggregate is greater than or equal to the preset compressive strength.

[0096] In the present invention, the raw materials for preparing the concrete containing modified recycled FRP aggregate preferably include coarse aggregate, fine aggregate, cement and water. The cement used in the embodiment is specifically OPC. The fine aggregate is specifically river sand.

[0097] In the present invention, the water-cement ratio in the mix ratio is 0.45. The mix ratio is the mass of water, cement, coarse aggregate and fine aggregate in the raw materials. In a specific embodiment of the present invention, the mix ratio of the concrete containing modified recycled FRP aggregate is 190:422:950:683.

[0098] In a specific embodiment of the present invention, the replacement rate is preferably 30-100%, and in the embodiment, it is specifically 30%, 50%, 70% or 100%. In the present invention, when the volume of the modified recycled FRP material accounts for less than 100% of the total volume of the coarse aggregate of the concrete containing the modified recycled FRP aggregate, the coarse aggregate of the concrete containing the modified recycled FRP aggregate preferably includes the modified recycled FRP material and natural coarse aggregate. The natural coarse aggregate is preferably stone.

[0099] In the present invention, the gradation selection of the modified recycled FRP material in the concrete mix has an important influence on the performance of the concrete. The present invention is preferably based on the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" GB / T50081-2019, "Pebbles and Crushed Stones for Construction" GB / T 14685-2011, and "Sand for Construction" GB / T14684-2011. Select and prepare the natural coarse aggregate, natural fine aggregate and recycled FRP aggregate required for concrete, determine the concrete mix ratio, and the experimental process ensures that the gradation of the recycled FRP aggregate is consistent with that of the natural coarse aggregate. The present invention preferably crushes the recycled FRP waste to obtain recycled FRP aggregates of different particle sizes, preferably in the range of 5 to 25 mm. In this way, the influence of different aggregate gradations on the strength of concrete after the recycled FRP particles replace natural aggregates can be minimized, and the aspect ratio of the recycled FRP particles is preferably controlled to a lower state (<1.6), so as to avoid the recycled FRP aggregate particles being too narrow and long and causing bad effects. The crushed FRP aggregate is tested for particle size distribution to ensure that the particle size distribution of the aggregate meets the design requirements. Aggregates with uniform particle size distribution can improve the density and strength of concrete. It should be noted that the crushing of recycled FRP is different from the crushing of ordinary natural aggregates, and it is necessary to use an electric saw to cut it into appropriate sizes. In addition, since there is a large amount of dust from resin and other fillers after the recycled FRP bars are crushed, and the surface of the natural coarse aggregate also has soil, both are rinsed with clean water, and then the natural coarse aggregate is placed in a drying box to dry, and the recycled GFRP aggregate is placed outdoors to dry. In the present invention, the recycled FRP material is subjected to the above-mentioned encapsulation modification to obtain the modified recycled FRP material, which is then used as all or part of the coarse aggregate in the preparation raw materials of the concrete.

[0100] In the present invention, the method for preparing the concrete is preferably: mixing the raw materials for preparing the concrete to obtain a slurry; pouring the slurry into a mold for first curing, and obtaining a molded body after demoulding; and subjecting the molded body to second curing to obtain the concrete product. The temperature of the first curing is preferably room temperature (25°C), and the time is preferably 24h. The second curing is preferably carried out in a standard curing room, and the temperature of the second curing is preferably 20±2°C, the time is preferably 28 days, and the relative humidity is preferably 95%.

[0101] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0102] Example 1

[0103] This embodiment designs 15 standard cylindrical compression test specimens (ф150mm×300mm). This embodiment mainly considers the volume replacement rate (r) of GFRP aggregate recycled from retired wind turbine blades (FRP aggregate recycled from retired wind turbine blades used in this embodiment) to natural coarse aggregate: 0%, 30%, 50%, 70%, 100%. The volume replacement rate r = FRP aggregate recycled from retired wind turbine blades / (FRP aggregate recycled from retired wind turbine blades + natural coarse aggregate); each volume replacement rate r has 3 repeated specimens to minimize the test error. The specific numbers of each group of specimens are shown in Table 1. For example, FRP30 means that the volume replacement rate r of GFRP aggregate recycled from retired wind turbine blades to natural coarse aggregate is 30%, and so on. The mix ratio of concrete in this embodiment (kg / m 3 ) as shown in Table 1. The water-cement ratio of this mix design is 0.45, which can make the compressive strength of the target cube (150mm×150mm×150mm cube) reach about 40MPa. All specimens were stored in an environment with a room temperature of about 25℃ after pouring and demolded after 24h. Then the specimens were placed in a standard curing room for 28 days. The temperature of the curing room was 20±2℃ and the relative humidity was 95%.

[0104] Table 1 Concrete mix ratio (kg / m 3 )

[0105]

[0106] The compression test was carried out using a 3000KNMTS servo hydraulic press, with a loading mode of displacement control of 0.3mm / min. The force was measured by a force sensor and the longitudinal displacement was monitored by four longitudinal LVDTs, and the data was collected on a computer through a Dewesoft dynamic acquisition box. The test results are summarized in Table 2. The results of the test show that as the volume replacement rate r of GFRP aggregate recycled from retired wind turbine blades to natural coarse aggregate increases, the compressive strength gradually decreases, and the reduction is relatively large: when the volume replacement rate r is 50%, the compressive strength decreases by 63.76%, and when the GFRP aggregate recycled from retired wind turbine blades completely replaces the natural coarse aggregate, the compressive strength is about one-seventh of the control group (FRP0). The elastic modulus of GFRP aggregate concrete (RFAC) recycled from retired wind turbine blades also gradually decreases with the increase of the volume replacement rate r of GFRP aggregate recycled from retired wind turbine blades. As for the peak strain, within the range of 0% to 50% of the volume replacement rate r, the peak strain first decreases and then increases with the increase of the volume replacement rate r; when the volume replacement rate r exceeds 50%, the same change pattern is also shown. In addition, Figure 2 The relationship between the replacement rate and compressive strength of recycled FRP aggregate concrete at different replacement rates is shown. Figure 3 The stress-strain curves of the axial compression test of GFRP aggregate concrete recycled from retired wind turbine blades under the condition of replacement rate r = 100% are compared with the experimental and predicted results. Figure 3 The replacement rate r = 100%, and the abscissa represents strain. The results show that although the experimental and predicted results of different volume replacement rates r of GFRP aggregates recycled from retired wind turbine blades are slightly different, they generally estimate the changes in stress and strain of GFRP aggregate concrete recycled from retired wind turbine blades under compression.

[0107] Table 2 Axial compression test results of FRP aggregate concrete specimens recycled from retired wind turbine blades

[0108]

[0109] Example 2

[0110] Epoxy mortar wrapping treatment:

[0111] ① Prepare the GFRP aggregate and epoxy mortar for recycling retired wind turbine blades, where the epoxy mortar includes epoxy resin (material A, Lica-131 carbon plate glue (Nanjing Haituo Composite Materials Co., Ltd.)), curing agent (material B), cement and quartz sand (material C, the mass ratio of cement to quartz sand is 1:2), several pallets and electronic scales;

[0112] ② Weigh the mass m of retired wind turbine blades to recycle GFRP aggregates, and weigh material A, material B, and material C in a mass ratio of 1:3:16; epoxy mortar coating amount s = mass of epoxy mortar / mass of GFRP aggregates recycled from retired wind turbine blades;

[0113] ③ Pour the GFRP aggregates recovered from retired fan blades into a small mixer, and pour the weighed C material into it, and then stir for 1 to 2 minutes to make the C material fully cover the surface of the GFRP aggregates recovered from retired fan blades;

[0114] ④ Mix the weighed material A and material B in a container and stir evenly, then start the mixer and slowly and evenly pour the mixture into the mixing drum;

[0115] ⑤ After the mixture is poured in, let the mixer continue to stir for 3 to 5 minutes, then take out the wrapped retired fan blades, recycle the GFRP aggregates, place them on a tray, and put them in the curing room for curing;

[0116] ⑥ After 48 hours of curing, take out the wrapped GFRP aggregates recovered from retired fan blades and pour them into the mixer again for stirring for 1 minute. The purpose is to separate some aggregates that are bonded together due to a small amount of epoxy mortar between the particles. Finally, pour out the GFRP aggregates recovered from retired fan blades and put them into the curing room for curing for 7 days.

[0117] In this embodiment, three modified FRP aggregates recycled from retired wind turbine blades with a mass ratio (encapsulation amount s) of epoxy mortar to GFRP aggregates recycled from retired wind turbine blades of 0.25, 0.3, and 0.35 were prepared for subsequent concrete pouring.

[0118] In this embodiment, 6 groups of modified GFRP aggregate concrete (MRFAC) recycled from retired wind turbine blades were designed, with 3 repeated specimens in each group, and a total of 18 standard cylindrical compressive specimens (ф150mm×300mm). The entire experiment involves two independent variables: the epoxy mortar coating amount s and the volume replacement rate r of the GFRP aggregate recycled from retired wind turbine blades to the natural coarse aggregate. On the one hand, the modified GFRP aggregate recycled from retired wind turbine blades was prepared with an epoxy mortar coating amount s of 0.25, and 4 groups of MRFAC specimens with different volume replacement rates r (30%, 50%, 70%, 100%) were designed to study the improvement of mechanical properties after modification. On the other hand, when the volume replacement rate r was 100%, the epoxy mortar coating amount s was changed to 0.3 and 0.35 respectively as the other 2 groups, and the influence of different epoxy mortar coating amounts on the compressive performance was analyzed. The specific numbers of each specimen are shown in Table 3. For example, FRP30-S0.25 means that the ratio of the epoxy mortar coating amount of the modified GFRP aggregate recycled from retired wind turbine blades to the mass of the GFRP aggregate recycled from retired wind turbine blades (epoxy mortar coating amount s) is 0.25, and the volume replacement rate r of the GFRP aggregate recycled from retired wind turbine blades to the natural coarse aggregate is 30%, and so on.

[0119] Table 3 Design of concrete specimens with GFRP aggregates recycled from modified retired wind turbine blades

[0120] Test piece Recycled GFRP aggregate replacement rate Epoxy mortar coating volume FRP30 30% 0 FRP50 50% 0 FRP70 70% 0 FRP100 100% 0 FRP30-S0.25 30% 0.25 FRP50-S0.25 50% 0.25 FRP70-S0.25 70% 0.25 FRP100-S0.25 100% 0.25 FRP100-S0.3 100% 0.30 FRP100-S0.35 100% 0.35

[0121] Table 4 shows the peak stress, corresponding peak strain and elastic modulus of modified GFRP aggregate concrete specimens with different GFRP replacement rates r. After the GFRP aggregates were wrapped with epoxy mortar, the overall compressive strength of the GFRP aggregates was significantly improved compared with the unmodified ones, with an increase of about 18%-86%. When the wrapping amount s was constant (s=0.25), the increase showed a trend of first decreasing and then increasing with the increase of the replacement rate. When the replacement rate r was 30%, the axial compressive strength of the modified concrete was 21.4% higher than that of the unmodified concrete, and it decreased slightly to 18.6% when the replacement rate r was 50%; and when the replacement rate r continued to increase to 70% and 100%, the increase was 29.4% and 72.2% respectively. This means that the epoxy mortar wrapping modification method has a better effect on initial defects (initial defects refer to the poor bonding between the interface of the GFRP aggregate recycled from retired wind turbine blades and the concrete matrix without epoxy mortar wrapping, the presence of holes, and the lower strength and elastic modulus.) The more modified GFRP aggregate concrete recycled from retired wind turbine blades, the better the compressive strength can be improved. In the specimens with the same replacement rate r (100%), the improvement of compressive strength by different wrapping amounts s is relatively close, about 70% to 86%, but the group with the best effect is the FRP100-S0.30 group.

[0122] Figure 4 The comparison of core compressive strength of modified recycled GFRP aggregate concrete is given.

[0123] Figure 5 The experimental and predicted results of the axial compressive stress-strain curve of the modified GFRP aggregate concrete recycled from retired wind turbine blades are compared. On the whole, the model proposed in the present invention has good performance at various replacement rates, especially when the epoxy mortar wrapping amount increases, the model curve shows a higher degree of consistency with the experimental curve. Figure 5 The substitution is when r is 100%, the wrapping amount s=0.25, the horizontal axis is strain, and the vertical axis is stress.

[0124] Table 4 Axial compression test results of modified recycled GFRP aggregate concrete specimens

[0125]

[0126]

[0127] The above can obtain the initial strength of ordinary concrete, the replacement strength of ordinary recycled FRP aggregate concrete at a replacement rate of recycled FRP from retired wind turbine blades, and the modified strength and epoxy mortar dosage of modified recycled FRP aggregate concrete from retired wind turbine blades at the replacement rate of recycled FRP. It is worth noting that the replacement rate of recycled FRP from retired wind turbine blades described in this embodiment includes 30%, 50%, 70% and 100%, but is not limited to this, and can include only a few of them, or can also include other multiple replacement rates, and the recycled FRP replacement rate can also be a non-integer value such as 9%, 17%.

[0128] Then, the stress-strain curves (strain on the horizontal axis, stress on the vertical axis), peak stress (concrete strength), initial slope (i.e., elastic modulus) and elastic modulus change characteristics before and after modification under different FRP replacement rates recycled from retired wind turbine blades were compared, and the constitutive equation of the peak stress of modified concrete with FRP aggregate recycled from retired wind turbine blades, the replacement rate of FRP aggregate recycled from retired wind turbine blades and the change of epoxy mortar wrapping amount was established.

[0129] According to the initial strength information and the replacement strength information, the present invention constructs an initial equation between the initial strength of ordinary concrete and the corresponding strength of ordinary recycled FRP aggregate concrete under any recycled FRP aggregate replacement rate, as shown in formula (1).

[0130] According to the modified strength information and the initial equation, the present invention constructs the target equations among the initial strength of ordinary concrete, the compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades, the replacement rate of FRP aggregate recycled from retired wind turbine blades and the epoxy mortar wrapping amount, such as formulas (2)-(6).

[0131] Finally, the present invention obtains the target parameters of the modified FRP aggregate concrete recycled from retired wind turbine blades, and inputs the data of the target parameters into the target equation, and the target equation outputs the current compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades; wherein the target parameters include the replacement rate of FRP recycled from retired wind turbine blades, the epoxy mortar wrapping amount, and the initial strength of ordinary concrete.

[0132] The present invention uses the constitutive equation to determine the compressive strength ( Figure 3 , Figure 5 ).

[0133] It is understandable that the prior art is unable to select other data (replacement rate of FRP aggregate recycled from retired wind turbine blades, epoxy mortar wrapping amount) based on the preset target strength and mix ratio of the modified FRP aggregate concrete recycled from retired wind turbine blades so that the compressive strength of the obtained modified FRP aggregate concrete recycled from retired wind turbine blades is greater than or equal to the preset target strength of the modified FRP aggregate concrete recycled from retired wind turbine blades.

[0134] In the present invention, the mix ratio of concrete and the preset target strength of the modified FRP aggregate concrete recycled from retired wind turbine blades are obtained, and the preset target strength is used as the compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades in the target formula, and the mix ratio is input into the target equation, the target equation outputs the data range of the parameters to be confirmed (replacement rate and packaging amount), and the target data of the parameters to be confirmed is determined according to the data range; the determined data and the target data are input into the target equation, and the target equation outputs the current compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades, so that the current compressive strength is above the preset target strength.

[0135] In a first implementation of the present invention, Figure 6It is a schematic diagram of the relationship between the replacement rate r of modified FRP aggregate recycled from retired wind turbine blades, the epoxy mortar coating amount s and the compressive strength of modified FRP aggregate concrete when the strength of ordinary concrete is 35MPa; the target strength of modified FRP aggregate concrete is determined by the concrete mix ratio, that is, the target parameter is the initial strength of ordinary concrete (natural aggregate concrete). The current initial strength of ordinary concrete and the preset target compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades are obtained, and the preset target strength is input as the compressive strength and the current initial strength into the target equation, and the target equation outputs the data ranges corresponding to the current substitution rate r and the current epoxy mortar coating amount s of the modified FRP aggregate concrete recycled from retired wind turbine blades; according to the data ranges corresponding to the current substitution rate and the current epoxy mortar coating amount of the modified FRP aggregate concrete recycled from retired wind turbine blades, the target substitution rate and the target epoxy mortar coating amount (i.e., the area above the design target plane) are determined; the initial strength, the target substitution rate and the target epoxy mortar coating amount are input into the target equation, and the target equation outputs the current compressive strength of the modified FRP aggregate concrete recycled from retired wind turbine blades, so that the current compressive strength is above the preset target strength.

[0136] The present invention sets concrete with the same mix ratio, adds a certain amount of FRP aggregate recycled from retired fan blades, changes the replacement rate of the FRP aggregate recycled from retired fan blades within a certain range, and uses different epoxy mortar wrapping amounts to modify the concrete so as to achieve the target strength.

[0137] As can be seen from the above embodiments, the present invention uses modified recycled waste FRP to replace natural stones (natural coarse aggregate) in concrete as coarse aggregate for concrete, which solves the problems of difficult FRP waste treatment and low resource utilization in the prior art, effectively reduces environmental pollution, and has important environmental significance. In addition, the present invention significantly improves the compressive strength and elastic modulus of recycled FRP aggregate concrete by coating the surface of recycled FRP aggregate with epoxy mortar, meeting the demand for high-performance building materials.

[0138] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing concrete containing modified recycled FRP aggregate, characterized in that: The following steps are involved: According to formulas (1) to (6), based on the preset compressive strength and mix ratio of the concrete containing the modified recycled FRP aggregate, the replacement rate and the encapsulation amount of the concrete containing the modified recycled FRP aggregate are obtained; the replacement rate is the volume percentage of the modified recycled FRP aggregate in the coarse aggregate of the concrete containing the modified recycled FRP aggregate, the modified recycled FRP aggregate is the recycled FRP aggregate modified by epoxy mortar, and the encapsulation amount is the mass ratio of the epoxy mortar to the recycled FRP aggregate; k s1 =1+0.449s 2 +0.928rs-0.699s (3); k s2 =-78.696s 2 -1.326rs+47.359s-5.921 (5); In formulas (1) to (6): f c ' is the compressive strength of concrete containing modified recycled FRP aggregate, f co ' is the compressive strength of concrete with natural aggregate, ε c ' is the peak strain of concrete containing modified recycled FRP aggregate, r is the substitution rate, k s1 k is the elastic modulus of concrete related to the amount of wrapping, s2 is the peak strain coefficient of concrete related to the encapsulation amount, s is the encapsulation amount, E c is the elastic modulus of concrete containing modified recycled FRP aggregate, k e is the elastic modulus coefficient of concrete related to the replacement rate; According to the wrapping amount, the recycled FRP material is wrapped and modified with epoxy mortar to obtain the modified recycled FRP aggregate; According to the replacement rate and the mix ratio, the modified recycled FRP aggregate is used to prepare the concrete containing the modified recycled FRP aggregate, and the compressive strength of the concrete containing the modified recycled FRP aggregate is greater than or equal to the preset compressive strength.

2. The preparation method according to claim 1, characterized in that: The method for determining the replacement rate and the package quantity comprises the following steps: The compressive strength of the concrete containing modified recycled FRP aggregate is preset, the preset compressive strength of the concrete containing modified recycled FRP aggregate is obtained, and the mix ratio of the concrete containing modified recycled FRP aggregate is determined; the compressive strength of the concrete containing natural aggregate is obtained from the mix ratio, and the range of two parameters, the replacement rate and the encapsulation amount, is obtained by using formulas (1) to (6), wherein the range is the range when the compressive strength of the concrete containing modified recycled FRP aggregate is ≥ the preset compressive strength under the condition of the determined mix ratio; and then the replacement rate and the encapsulation amount of the concrete containing modified recycled FRP aggregate are determined from the range of the two parameters, the replacement rate and the encapsulation amount.

3. The preparation method according to claim 1 or 2, characterized in that: The packaging amount is 0.1-0.5; the replacement rate is ≥30%.

4. The preparation method according to claim 1, characterized in that: The epoxy mortar comprises epoxy resin, a curing agent and an auxiliary agent; the auxiliary agent comprises cement and quartz sand.

5. The determination method according to claim 4, characterized in that: The mass ratio of the epoxy resin, the curing agent and the auxiliary agent is (1-2): (1-5): (12-20).

6. The preparation method according to claim 4, characterized in that: The mass ratio of cement to quartz sand in the auxiliary agent is 1:(1-3).

7. The preparation method according to claim 1, characterized in that: The particle size of the recycled FRP material ranges from 5 to 25 mm, and the aspect ratio is less than 1.

6.

8. The preparation method according to claim 1, characterized in that: The package modification comprises the following steps: premixing the recycled FRP material and an additive to obtain a premix; The epoxy resin and the curing agent are mixed and then mixed with the premix to obtain an initial modified product; The initial modified product is cured to obtain the modified recycled FRP aggregate.

9. The preparation method according to claim 1, characterized in that: The water-cement ratio in the mix is ​​0.

45.

10. The preparation method according to claim 1, characterized in that: The curing conditions for preparing the concrete containing the modified recycled FRP aggregate include: a curing temperature of 20±2° C., a relative humidity of 95%, and a curing time of 28 days.

Citation Information

Patent Citations

  • Method for detecting intensity of solid structure concrete by impact elastic wave method

    CN108362580A

  • Recycled aggregate pervious concrete based on waste glass particles, preparation method and modification identification method

    CN115010422A

  • Mix proportion design method and manufacturing method for concrete with coarse aggregate replaced by steel slag

    CN116759025A

  • Recycled frp aggregate and cement-based hardened body using the aggregate

    JP2003321261A